Pricing equity warrants with jumps, stochastic volatility, and stochastic interest rates - Ibrahim, S. N. I.; Sawal, A. S.; Roslan, T. R. N. (Lviv Polytechnic National University, 2022)
A warrant is a derivative that gives the right, but not the obligation, to buy or sell a security at a certain price before the expiration. The warrant valuation method was inspired by option valuation because of the certain similarities between these two derivatives. The warrant price formula under the Black–Scholes is available in the literature. However, the Black–Scholes formula is known to have a number of flaws; hence, this study aims to develop a pricing formula for warrants by incorporating jumps, stochastic volatility, and stochastic interest rates into the Black–Scholes model. The closed-form pricing formula is presented in this study, where the derivation involves stochastic differential equations (SDE), which include the Cauchy problem and heat equation.